2007
DOI: 10.1590/s0037-86822007000200020
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da contaminação de hortas produtoras de verduras após a implantação do sistema de fiscalização em Ribeirão Preto, SP

Abstract: This study evaluated the microbiological and parasitological contamination of 88 market gardens producing green vegetables, of which 47 had been investigated previously. The contamination rate was 38.3% in the market gardens previously evaluated and 43.9% in the new market gardens. Food safety requires a continuous and efficient sanitary surveillance system for market gardens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
18

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 7 publications
(2 reference statements)
1
1
0
18
Order By: Relevance
“…According to these authors, inappropriate sanitary conditions of the irrigation water used in farming are the main cause of contamination of lettuce in this production system. This hypothesis may be confirmed by results presented by Takayanagui et al (2007), who found faecal coliform contamination and intestinal parasites in leafy vegetables' irrigation water.…”
Section: Neressupporting
confidence: 71%
“…According to these authors, inappropriate sanitary conditions of the irrigation water used in farming are the main cause of contamination of lettuce in this production system. This hypothesis may be confirmed by results presented by Takayanagui et al (2007), who found faecal coliform contamination and intestinal parasites in leafy vegetables' irrigation water.…”
Section: Neressupporting
confidence: 71%
“…Takayanagui et al (2007), avaliando a contaminação de hortas em Ribeirão Preto -SP, verificaram contaminação em 40,9% das 88 hortas produtivas, sendo que das 103 águas de irrigação analisadas, 15,5% estavam em desacordo com a legislação em vigor. Sandri (2003), estudando a aplicação de água residuária de origem doméstica após tratamento em leito cultivado com macrófitas na cultura de alface, não encontrou a presença de coliformes termotolerantes nas folhas de alface quando aplicadas por gotejamento superficial ou subterrâneo, porém sua presença foi detectada quando utilizou a irrigação por aspersão.…”
Section: Resultsunclassified
“…De acordo com Silva et al (2005) e Wichert (2005), as perdas de espécies químicas e matéria orgânica acompanham as perdas de solo, sendo encontrado nos sedimentos de erosão a seguinte tendência, em ordem decrescente: Ca>K>Mg>P, não concordando com Oliveira (2007) que apresenta a seguinte ordem: Ca>Mg>K>P. Corroborando com a afirmação de Oliveira (2007), Pinheiro et al (2010), ao analisarem sedimento erodido em cultura de eucalipto sob chuva natural obtiveram 11,42 kg ha -1 de perdas totais de nutrientes, representadas por 63% de Ca, 18% de Mg, 13% de K e 6% de P.…”
Section: Introductionunclassified
“…O solo parece ser o responsável pela maioria das contaminações, seguido da utilização de água não tratada para irrigação e condições impróprias de lavagem e estocagem (ODUMERU et al, 1997). Takayanagui et al (2007), avaliando a contaminação de hortas em Ribeirão Preto -SP, verificou contaminação em 40,9% das 88 hortas produtivas, sendo que das 103 fontes de água de irrigação analisadas, 15,5% estavam em desacordo com a legislação em vigor.…”
Section: Análise Microbiológica De Tomatesunclassified